Python ethical hacking from scratch : think like an ethical hacker, avoid detection, and successfully develop, deploy, detect, and avoid malware /: think like an ethical hacker, avoid detection, and successfully develop, deploy, detect, and avoid malware. (2021) - Sarwar, Fahad Ali
No abstract available